Challenges in migrant women's maternity care in a high-income country: A population-based cohort study of maternal and perinatal outcomes - Gudmundsdottir Embla Y; Gottfredsdottir Helga; Halfdansdottir Berglind; Nieuwenhuijze Marianne; Gissler Mika; Einarsdottir Kristjana (WILEY, 2022)
Introduction This study aims to explore maternal and perinatal outcomes of migrant women in Iceland.Material and methods This prospective population-based cohort study included women who gave birth to a singleton in Iceland between 1997 and 2018, comprising a total of 92 403 births. Migrant women were defined as women with citizenship other than Icelandic, including refugees and asylum seekers, and categorized into three groups, based on their country of citizenship Human Development Index score. The effect of country of citizenship was estimated. The main outcome measures were onset of labor, augmentation, epidural, perineum support, episiotomy, mode of birth, obstetric anal sphincter injury, postpartum hemorrhage, preterm birth, a 5-minute Apgar <7, neonatal intensive care unit admission and perinatal mortality. Odds ratios (ORs) and 95% confidence intervals (CIs) for maternal and perinatal outcomes were calculated using logistic regression models.Results A total of 8158 migrant women gave birth during the study period: 4401 primiparous and 3757 multiparous. Overall, migrant women had higher adjusted ORs (aORs) for episiotomy (primiparas: aOR 1.43, 95% CI 1.26-1.61; multiparas: 1.39, 95% CI 1.21-1.60) and instrumental births (primiparas: 1.14, 95% CI 1.02-1.27, multiparas: 1.41, 95% CI 1.16-1.72) and lower aORs of induction of labor (primiparas: 0.88, 95% CI 0.79-0.98; multiparas: 0.74, 95% CI 0.66-0.83), compared with Icelandic women. Migrant women from countries with a high Human Development Index score (>= 0.900) had similar or better outcomes compared with Icelandic women, whereas migrant women from countries with a lower Human Development Index score than that of Iceland (<0.900) had additionally increased odds of maternal and perinatal complications and interventions, such as emergency cesarean and postpartum hemorrhage.Conclusions Women's citizenship and country of citizenship Human Development Index scores are significantly associated with a range of maternal and perinatal complications and interventions, such as episiotomy and instrumental birth. The results indicate the need for further exploration of whether Icelandic perinatal healthcare services meet the care needs of migrant women.